Снижение потерь в пусковых режимах асинхронного двигателя при скалярном частотном управлении - Чекавский, Глеб Станиславович; Розкаряка, Павел Иванович; Мельник, Артем Анатольевич (НТУ "ХПИ", 2010)
The paper shows the main results of numerical research the energy efficiency of V/f-control laws for starting the variable-frequency induction motor. Some possibilities for minimization the power of losses during starting the motor by correcting the laws of V/Fcontrol has been shown.
Decreasing the power losses during starting of induction motor in v/f-control systems
Keywords: электропривод; сопротивление; статор; ротор; управление частотное; инерция